Population of epiphytic algae on enhalus acoroides in Ali Cove, Taklong Island, Nueva Valencia, Guimaras. - Maglantay, Jeffrey Sumcad
Epiphytic algae, although they play a significant role in maintaining the organizational balance of the complex marine ecosystem, are one of the least studied marine organisms. The study sought to add more information on the composition, distribution and abundance of epiphytic algae on Enhalus acoroides in Ali Cove, Taklong Island, Nueva Valencia, Guimaras., Four transect lines were laid perpendicular to the shore with 20m interval between transect lines to cover the entire area. Five shoots of Enhalus acoroides were randomly harvested in the five plots of each transect line. Results of the study showed that blue-green algae have the highest relative frequency of 55.09 percent. In previous studies conducted by Alojado (1994) and Sedonio (1996), red algae had the highest relative frequency of 40 percent of the total number of epiphyte species in Ali Cove and 36 percent in Kalaparan, respectively. This deviation in the previous studies could be due to some temporal deviations exhibited by epiphytic algae community all throughout the year. The dominance of blue-green is attributed to the flexibility and adaptiveness of some blue-green algae species to extreme conditions. Water temperature in the entire study are during the sampling ranges from 28-32 degrees centigrade. Water salinity and pH values range from 25-26 ppt. and 8.47-9.23, respectively.